Lifestyle Medicine in Latin America: Medicina del Estilo de Vida en Latinoamérica - De La Cruz-Vargas, Jhony A. (2021)
It is a pleasure to start the year 2022 with the special edition of the first issue of our journal dedicated to "Lifestyle Medicine in Latin America". The growth of this new medical discipline at a global level, considered as the seventh era of public health, with a level of scientific evidence that positions it as one of the areas of greatest production and publications at an international level. Only in PubMed there are more than 60 thousand indexed articles.